Gas Chromatography-Mass Spectrometry (GC-MS) Analysis of Volatile Components from Guava Leaves. Issue 6 (2nd November 2017) - Xu, Chang; Liang, Zhengang; Tang, Dan; Xiao, Tongjie; Tsunoda, Makoto; Zhang, Yingxia; Zhao, Lini; Deng, Shiming; Song, Yanting
Abstract: In this paper, the volatile components extracted from guava leaves by steam distillation (SD) was investigated and comprehensively analyzed for the first time. To obtain more sensitive and accurate analysis, the sample preparation procedure for Gas Chromatography-Mass Spectrometry (GC-MS) analysis of the volatile compounds was investigated and then 27 compounds were identified in the samples obtained by SD method. The volatile components in guava leaf were made up largely of sesquiterpenoids, including α-cubebene, caryophyllene, aromadendrene, α-cadinene, and calamenene. The results indicated that the volatile components from the guava leaves extracted by SD technology was quite different, and the research provided comprehensive information for the volatile compounds in the guava leaves.